2007
DOI: 10.1186/1472-698x-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of HIV counselling and testing among tuberculosis patients in south Ethiopia

Abstract: BackgroundTo benefit from available care and treatment options, patients should first be counselled and tested for HIV. Our aim was to assess the acceptability of HIV testing among tuberculosis patients under routine care conditions in south Ethiopia.MethodsWe interviewed all adult tuberculosis patients who were treated at Arba Minch Hospital in Ethiopia between January and August 2005. After recording socio-demographic information and tuberculosis treatment history, we referred those patients who showed initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 10 publications
9
33
2
Order By: Relevance
“…This might be due the high prevalence of HIV/AIDS infection in this age group which could have made them susceptible to TB. The findings of this study (high prevalence of TB occurred in the young (<29) population) is similar to findings documented by several studies and the WHO (Jerene, Endale and Lindtjorn, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This might be due the high prevalence of HIV/AIDS infection in this age group which could have made them susceptible to TB. The findings of this study (high prevalence of TB occurred in the young (<29) population) is similar to findings documented by several studies and the WHO (Jerene, Endale and Lindtjorn, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…The number of population willing to accept PIHCT was the main outcome variable used to calculate the sample size and a study conducted in Arbaminch Town shows the prevalence of willingness to accept PIHCT was 35% among cases (Jerene, Endale and Lindtjorn, 2007) and 50% among controls were assumed to consider maximum sample size since there is no similar study done, with 5% marginal error and 95% confidence interval, and 80% power. Assuming 15% non-response rate, the minimum sample size was calculated to be 473 for both groups using the formula for difference between population proportions.…”
Section: Sample Size Determination and Sampling Proceduresmentioning
confidence: 99%
“…17 In contrary, the mean age in this study was found to be 36.49 years (±13.77), however was similar to other studies. (18)(19)(20)(21) Similar to this study, there is a higher male preponderance in the diseased state as reported in a study done among people with HIV/TB co-infection as well as those fielded in WHO global tuberculosis report.…”
Section: Socio-demographic Profile Of Participantssupporting
confidence: 88%
“…35,36 Although they provided evidence of the feasibility of PITC, these studies did not reflect patients' experiences of or views about PITC. Our review of the published literature suggests that PITC is generally acceptable to patients.…”
Section: Discussionmentioning
confidence: 99%